A RARE CASE OF FACIAL DYSMORPHISM IN A GOAT KID - RAJAT; GANDOTRA, V K; SINGH, NAVDEEP; GHUMAN, S P S (The Indian Journal of Animal Reproduction, 2016)
A rare case of dystocia due to fore limb retention, facial dysmorphism with multiple abnormalities and neck enlargement in a goat kid was relieved following gentle traction on head and fore limbs.